Characterization and phase evolution of cordierite based glass synthesis from pure oxide and minerals - Banjuraizah, Johar; Hasmaliza, Mohamad; Zainal Ariffin, Ahmad (Trans Tech Publications, Switzerland, 2011)
Link to publisher's homepage at www.ttp.net/